2007
DOI: 10.1590/s0001-37652007000400002
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of the extracts and saponins from Sapindus saponaria L.

Abstract: Extracts from the dried pericarp of Sapindus saponaria L. (Sapindaceae) fruits were investigated for their antifungal activity against clinical isolates of yeasts Candida albicans and C. non-albicans from vaginal secretions of women with Vulvovaginal Candidiasis. Four clinical isolates of C. albicans, a single clinical isolated of each of the species C. parapsilosis, C. glabrata, C. tropicalis, and the strain of C. albicans ATCC 90028 were used. The hydroalcoholic extract was bioactivity-directed against a cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 15 publications
3
37
0
5
Order By: Relevance
“…This higher antifungal activity might be related with the solubility of the active principles in the solvents used; phenolic compounds are one of the most abundant bioactive molecules present in those polar extracts. (Webster et al, 2008) C. krusei 12.5 mg/mL C. lusitaniae 12.5 mg/mL C. parapsilosis 12.5 mg/mL Adiantum capillus veneris C. albicans 1 mg/mL * (Ishaq et al, 2014) Allium sativum C. albicans 0.2 mg/mL (Shamim et al, 2004) 100 mg/mL * (Fei et al, 2008) 1 mg/mL * (Pathak, 2012) C. dublinensis 1 mg/mL * (Pathak, 2012) C. grabrata 0.2 mg/mL (Shamim et al, 2004) 1 mg/mL * (Pathak, 2012) C. krusei 100 mg/mL * (Fei et al, 2008) 1 mg/mL * (Pathak, 2012) C. tropicalis 0.2 mg/mL (Shamim et al, 2004) 100 mg/mL * (Fei et al, 2008) 1 mg/mL * (Pathak, 2012) Alnus viridis C. albicans 12.5 mg/mL (Webster et al, 2008) C. glabrata 25 mg/mL C. krusei 0.2 mg/mL C. lusitaniae 6 mg/mL C. parapsilosis 25 mg/mL C. tropicalis 3 mg/mL (Jasim and Al-khaliq, 2011) C. parapsilosis 2.5 mg/mL (Martins et al, 2015) C. tropicalis 1.25 mg/mL (Martins et al, 2015) Sapindus saponaria C. parapsilosis 0.16 mg/mL (Tsuzuki et al, 2007) Scutellaria baicalensis C. albicans 2.5 mg/mL (Wong and Tsang, 2009) C. glabrata 6.25 mg/mL C. guilliermondii 3.12 mg/mL C. krusei 3.12 mg/mL C. lusitaniae 1.56 mg/mL C. parapsilosis 3.12 mg/mL C. tropicalis 3.12 mg/mL * Dichloromethane extracts. MIC -Minimum inhibitory concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This higher antifungal activity might be related with the solubility of the active principles in the solvents used; phenolic compounds are one of the most abundant bioactive molecules present in those polar extracts. (Webster et al, 2008) C. krusei 12.5 mg/mL C. lusitaniae 12.5 mg/mL C. parapsilosis 12.5 mg/mL Adiantum capillus veneris C. albicans 1 mg/mL * (Ishaq et al, 2014) Allium sativum C. albicans 0.2 mg/mL (Shamim et al, 2004) 100 mg/mL * (Fei et al, 2008) 1 mg/mL * (Pathak, 2012) C. dublinensis 1 mg/mL * (Pathak, 2012) C. grabrata 0.2 mg/mL (Shamim et al, 2004) 1 mg/mL * (Pathak, 2012) C. krusei 100 mg/mL * (Fei et al, 2008) 1 mg/mL * (Pathak, 2012) C. tropicalis 0.2 mg/mL (Shamim et al, 2004) 100 mg/mL * (Fei et al, 2008) 1 mg/mL * (Pathak, 2012) Alnus viridis C. albicans 12.5 mg/mL (Webster et al, 2008) C. glabrata 25 mg/mL C. krusei 0.2 mg/mL C. lusitaniae 6 mg/mL C. parapsilosis 25 mg/mL C. tropicalis 3 mg/mL (Jasim and Al-khaliq, 2011) C. parapsilosis 2.5 mg/mL (Martins et al, 2015) C. tropicalis 1.25 mg/mL (Martins et al, 2015) Sapindus saponaria C. parapsilosis 0.16 mg/mL (Tsuzuki et al, 2007) Scutellaria baicalensis C. albicans 2.5 mg/mL (Wong and Tsang, 2009) C. glabrata 6.25 mg/mL C. guilliermondii 3.12 mg/mL C. krusei 3.12 mg/mL C. lusitaniae 1.56 mg/mL C. parapsilosis 3.12 mg/mL C. tropicalis 3.12 mg/mL * Dichloromethane extracts. MIC -Minimum inhibitory concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit extracts present antifungical (Tsuzuki et al, 2007), larvicidal (Silva et al, 2004;Fernandes et al, 2005;Barreto et al, 2006), and bleeding neutralizer activities (Castro et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The use of Sapindus mukorossi in folk medicine worldwide 30 is validated by scientific studies that have demonstrated the efficacy of the extracts in various experimental models. Pharmacological effects of Sapindus mukorossi have been reported like anti-bacterial 19 , insecticidal 12,13,26 , spermicidal 11,27 , anti-trichomonas 11,39 , anti-tumor 22,29,36 , hepatoprotective 18 , anxiolytic 1 , molluscicidal 16,42 , fungicidal 37,41 , antiinflammatory 35 and piscicidal 44 activities and are being employed for the treatment of different ailments in the indigenous system of medicine. Although a number of phytochemicals present in Sapindus mukorossi have been isolated and identified by researchers working in different laboratories, their pharmacological/biological studies in human welfare has not been studied so far.…”
Section: Discussionmentioning
confidence: 99%
“…The major compounds isolated from Sapindus mukorossi are triterpenoidal saponins of mainly three oleanane, dammarane and tirucullane types. Recently many of the pharmacological actions of this plant have been explored which includes the antimicrobial 19 , cytotoxic 29 , molluscicidal 16,42 , insecticidal 12,26 , piscicidal 44 and fungicidal 37,41 activities. One of the most talked about activities of this plant is the contraceptive activity of the saponins extracted from the pericarp of the fruit 11,27 .…”
Section: Introductionmentioning
confidence: 99%